Synthesis and Antitumor Activity of Some Pyrazole Derivatives - E.M. El-Baih, Fatma; M. Al-Hazimi, Hassan (Asian Journal of Chemistry, 2010)
Vilsmeier-Haack chloroformylation of 1a-e using DMF and an excess of POCl3 yielded the corresponding pyrazole-4-carbaldehydes 2a-e. Reaction of 2a,c with o-bromophenol and KOH in DMF gave the target compound 5-phenoxypyrazole-4-carbaldehydes 3a,b which in turn gave the corresponding oximes 4a,b by oximation of 3a,b with hydroxylamine. Condensation of 2b,c with 1,2-diaminobenzene and 2-aminothiophenol was carried out to give tetrahydrobenzo- [b]pyrazolo[3,4-e][1,4]diazepine derivatives 5a,b and benzo[b]pyrazolo[4,3-f][1,4]thiazepine derivatives 6a,b, respectively. Some of the prepared compounds was examined as cytotoxic agents. The compounds 3a, 4a, 5a and 6a were proved to be less or more active than the standared doxorubicin depending on the cell lines.